LGBT Museums and Communities: Mapping actions to overcome diversity phobias in museums and community initiatives around the globe (Cadernos de Sociomuseologia, 2017)
This study seeks an overall view of the memory of the LGBT community (lesbian, gay, bisexual, transgender) in museums and community initiatives, the project LGBT memory mapping and analyzes the main existing shares in Europe, the Americas, Africa, Asia and Oceania. Through technical visits, interviews, non-directive (attendance or virtual), the magazine LGBT Memory publications, bibliographical researches and queries to official sites, mapping aims to indicate the limits and possibilities that are presented to museological field by including a minority present in every continent but still forgotten. This museological invisibility, favors forgetfulness and consequently strengthens phobias of sexual orientation and gender identity. By analyzing the preservation techniques, the exhibition content of each mapped proposal and its absence in large territories, looking to indicate strategies found in building a global LGBT memory, questioning, therefore, the democratization of memory and manifest content in museums, community initiatives or museological policies interested in winning civil rights and overcoming phobias to sexual / emotional diversity.Keywords: LGBT, Diversity, Social Museology